DYNAMIC STABILITY ANALYSIS OF ADVANCED SUPPORT EQUIPMENT - XIE Miao; ZHAO ChunXiao; BAI YaJing (Jixie qiangdu)
Advanced support equipment is used for comprehensive tunneling roadway temporary support equipment,in order to improve the stability and optimize the structure of the advanced support equipment,carry on the dynamic stability analysis,establish advanced support equipment mainly for components-column dynamics model,and establish the parameters of the vibration differential equation,its dynamic stability region and the dynamic instability region,using the energy method to analyze the stability of the columns,to provide the basis for advanced support equipment dynamic stability criterion later.